Management in the prevention of suicide behavior of users of Primary Health Care: Systematic review (Research, Society and Development, 2021)
Suicidal behavior is characterized by any action in which the human being causes harm to himself. Taking into account that Primary Health Care (PHC) is the preferred gateway for users to health services, this scenario starts to play a crucial role in the identification, management and prevention of the ascribed behavior. Thus, the objective was to review, in the scientific literature, how the prevention of self-extermination behavior of PHC users is carried out by the interdisciplinary team of the health service. For this, a systematic review was carried out, following the PRISMA guidelines, based on Brazilian studies published, in the format of an original scientific article, in the SciELO and LILACS database, between the years 2016 and 2021. 28 articles were recovered, of which 7 were selected according to the inclusion criteria, to compose the sample. It was found that although PHC has strategies to act preventively in the management of behavior aimed at self-extermination, among these, the ease of creating bonds, patient care, identification, assessment and regular monitoring of the individual and of risk factors , the possibility of triggering protective factors and home visits, professionals still demonstrate incapable and helpless to exercise the management of their users. In this sense, it suggests new studies on the subject, involving proposals and solutions to solve the difficulties encountered by these professionals, as well as adequate training and the development of strategies to prevent this phenomenon.